2013
DOI: 10.1097/rli.0b013e3182839c2b
|View full text |Cite
|
Sign up to set email alerts
|

Nonenhanced Magnetic Resonance Angiography of the Lower Extremity Vessels at 7 Tesla

Abstract: The results of our study demonstrate the feasibility of non-contrast-agent-enhanced MRA of the lower extremity vessels at 7 T. Nonenhanced MRA of the lower extremities at this very high magnetic field can be considered to be in an early but promising stage. Further sequence optimization and the examination of a larger number of participants as well as comparison with contrast-enhanced MRA and nonenhanced techniques at lower field strengths should be pursued in future trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 35 publications
3
21
0
Order By: Relevance
“…TOF MRA revealed its diagnostic superiority due to high vessel-tobackground contrast compared to FLASH imaging [70]. The application of non-enhanced ultra-high-field MRA has recently also been successfully expanded to imaging of the vessels of the lower extremities [71] ( • " Fig. 8).…”
mentioning
confidence: 99%
“…TOF MRA revealed its diagnostic superiority due to high vessel-tobackground contrast compared to FLASH imaging [70]. The application of non-enhanced ultra-high-field MRA has recently also been successfully expanded to imaging of the vessels of the lower extremities [71] ( • " Fig. 8).…”
mentioning
confidence: 99%
“…However, we observed that during increased HRV, an artifact associated with inaccurate triggering [12] appeared in the MRA images. This is interesting because the triggers were quantitatively more similar to PO than during another scan that contained no artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments were performed on an ultra-high-field whole-body MRI system (MAGNETOM 7T; Siemens GmbH, Erlangen, Germany) using the MRA setup as described by Fischer et al [12] with a 16-channel transmit/receive body coil [34]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations